Preventing the displacement of small businesses through commercial gentrification: are affordable workspace policies the solution?. (7th August 2016) - Ferm, Jessica
Abstract: The displacement of small businesses in cities with rising land values is of increasing concern to local communities and reflected in the literature on commercial or industrial gentrification. This article explores the perception of such gentrification as both a problem and an opportunity, and considers the motivations and implications of state intervention in London, where policies requiring affordable workspace to be delivered within mixed use developments have been introduced. Based on case studies of 13 mixed use developments in London, the findings reveal the limitations and unintended consequences of affordable workspace policies, leading to a call for planners to revisit and strengthen more traditional planning tools.